Growing like China revisit : a quantitative analysis during 1998 -- 2015 - Long, Haiyan (2017)
The growth pattern of the Chinese economy since 1990s is very controversial: the high output growth is accompanied by sustained increases in returns on capital, investment rates, and saving rates. Song et al. (2011) have proposed a theory of economic transition which can comprehensively explain Chinese experience from 1992 to 2007. But from 2008 onwards, due to the global recession and financial crisis, the Chinese economy has experienced tremendous changes including government’s four-trillion-Yuan stimulus package, the reform of state-owned firms and the revolution in the capital market. Therefore, we modify Song’s model to mimic China’s economic development until 2015. The private firms operated by entrepreneurs are more productive, but the financial imperfections force them to rely on internal savings to raise capital. State-owned firms with low-productivity depend on their superiority in the financial market to remain in the game. As the financial market in China becomes more developed, financial frictions gradually decrease; meanwhile, the continuous growth of the saving rate increases entrepreneurial firms’ capital stock and relaxes the limits of the high-productivity firms’ growth. While the calibrated model, in general, captures the features of the Chinese economy, it no longer matches as perfectly as before. This is likely due to the government intervention, housing bubble, foreign direct investments and overseas investments.